Analyses Mutations in GSN, CST3, TTR, and ITM2B Genes in Chinese Patients With Alzheimer’s Disease - Jiang, Yaling; Jiao, Bin; Liao, Xinxin; Xiao, Xuewen; Liu, Xixi; Shen, Lu (Frontiers in Aging Neuroscience, 2020)
Amyloid protein deposition is a common mechanism of hereditary amyloidosis (HA) and Alzheimer's disease (AD). Mutations of gelsolin (GSN), cystatin C (CST3), transthyretin (TTR) and integral membrane protein 2B (ITM2B) genes can lead to HA. But the relationship is unclear between these genes and AD. Genes targeted sequencing (GTS), including GSN, CST3, TTR and ITM2B, was performed in a total of 636 patients with clinical AD and 365 normal controls from China. As a result, according to American College of Medical Genetics and Genomics (ACMG) guidelines, two novel likely pathogenic frame-shift mutations (GSN:c.1036delA:p.K346fs and GSN:c.8_35del:p.P3fs) were detected in five patients with AD, whose initial symptom was memory decline, accompanied with psychological and behavioral abnormalities later. Interestingly, the patient with K346fs mutation, presented cerebral β-amyloid protein deposition, had an early onset (48 years) and experienced rapid progression, while the other four patients with P3fs mutation had a late onset ((Mean±SD): 69.50±5.20 years) and a long course of illness ((Mean±SD): 9.24±4.86 years). Besides, we also discovered 17 variants of uncertain significance (VUS) in these four genes. To our knowledge, we are the first to report AD phenotype with GSN mutations in patients with AD in the Chinese cohort. Although mutations in the GSN gene are rare, it may explain a small portion of clinically diagnosed AD.